Optimalisasi Pemberdayaan Masyarakat Dalam Pembuatan Olahan Jeruk Sebagai Inovasi Komoditas Unggulan Di Desa Lolo Hilir, Kecamatan Bukit Kerman, Kabupaten Kerinci - Fadli Anugrah; Gampo Haryono; Deky Hamdani; Ayu Esteka Sari; Trian Jaka Ronaldo (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the Tri Dharma College activities is community service which provides learning and working experiences in activities to increase potential for the community. The purpose of community service is to implement a product downstream strategy in overcoming abundant production for orange plants in Lolo Hilir Village, Bukit Kerman District, Kerinci Regency. The methods used are field observation, interviews and delivering material. The target population is the community in Lolo Hilir Village. The results of community service in the form of implementing assistance to the community to understand product downstream strategies in overcoming abundant production for orange plants, helping the preparation of supporting facilities for downstream oranges into processed products. Through this activity, the community feels a change in the form of increasing knowledge, and community income can increase.